2016
DOI: 10.1002/glia.23016
|View full text |Cite
|
Sign up to set email alerts
|

Microglial phagocytosis and activation underlying photoreceptor degeneration is regulated by CX3CL1‐CX3CR1 signaling in a mouse model of retinitis pigmentosa

Abstract: Retinitis pigmentosa (RP), a disease characterized by the progressive degeneration of mutation-bearing photoreceptors, is a significant cause of incurable blindness in the young worldwide. Recent studies have found that activated retinal microglia contribute to photoreceptor demise via phagocytosis and pro-inflammatory factor production, however mechanisms regulating these contributions are not well-defined. In this study, we investigate the role of CX3CR1, a microglia-specific receptor, in regulating microgli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
126
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(155 citation statements)
references
References 66 publications
14
126
3
Order By: Relevance
“…Since there was no differentiation in those studies between MG and the population we have identified as GFP hi cells detectable in the CD11c GFP mice, it is unclear if functions attributed to MG were instead being mediated by the GFP hi cells we have described. The extensive infiltration of retinal macrophages into the subretinal space found by Zabel et al [41] in the rd10 model were not recapitulated in our study of the Rpe65 −/− mice; relatively few GFP hi cells were found in the OS, and only rare cells were found on the RPE. An important difference in the models is that cones are greatly outnumbered by rods, 1.8 × 10 5 cones versus 6.4 × 10 6 rods [42], so that rod degeneration may have a much larger impact on retinal homeostasis.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Since there was no differentiation in those studies between MG and the population we have identified as GFP hi cells detectable in the CD11c GFP mice, it is unclear if functions attributed to MG were instead being mediated by the GFP hi cells we have described. The extensive infiltration of retinal macrophages into the subretinal space found by Zabel et al [41] in the rd10 model were not recapitulated in our study of the Rpe65 −/− mice; relatively few GFP hi cells were found in the OS, and only rare cells were found on the RPE. An important difference in the models is that cones are greatly outnumbered by rods, 1.8 × 10 5 cones versus 6.4 × 10 6 rods [42], so that rod degeneration may have a much larger impact on retinal homeostasis.…”
Section: Discussioncontrasting
confidence: 93%
“…The TAM-mediated protection was found in mice lacking creER-linked ablation of CX3CR1 + cells, suggesting that TAM has neuroprotective properties that inhibit of macrophage activation [40]. MG/macrophage involvement in rod photoreceptor degeneration in the rd10 mouse model for retinitis pigmentosa was found to be mediated by primary phagocytosis of living rod photoreceptor cells through a CX3CL1-CX3CR1 mediated signaling pathway [37, 41]. Since the retinal degeneration models cited above yield substantial retinal damage, the potential for participation of monocyte-macrophages recruited from the circulation is present, and experiments to rule out their contributions were not done.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting revealed an increase in 100kDa fractalkine protein at P20 and P25 with Norgestrel (Fig 8C; red boxes). This isoform is neuroprotective in the retina by dampening harmful microglial processes and consequently improving photoreceptor survival [57, 62]. Immunofluorescence on retinal sections also showed an increase in fractalkine with Norgestrel (Fig 8D).…”
Section: Resultsmentioning
confidence: 99%
“…Fractalkine signaling has been shown to prevent cell loss in a number of different disease models [56, 61, 6770]. In mouse models of RP, CX3CR1 -/- rd10 mice experience a worsened disease progression [19] and intravitreal injection of recombinant full-length fractalkine improves photoreceptor survival in the rd10 mouse [62]. Indeed we show that rd10 microglia pre-treated with full-length fractalkine cause significantly less 661W cell death in co-culture (Fig 8E and 8F).…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, the cells retract their protrusions and transform into amoeboid phagocytes that can produce a variety of neurotoxic inflammatory mediators including reactive oxygen species and cytokines 8 . Reactive microglia clear dying neurons but can also damage and phagocytose whole living photoreceptors in the diseased developing retina 9,10 . Under specific conditions of retinal lipid accumulation, intraretinal or subretinal microglia appear as lipid-bloated cell aggregates 11,12 .…”
Section: Introductionmentioning
confidence: 99%